Evaluation of three commercial SARS-CoV-2 serology assays in a tertiary care hospital in the United Arab Emirates. Issue 7 (July 2021) - Alatoom, Adnan; Atef, Shereen; AbdelWareth, Laila; Murthy, Jay; Jones, Matthew; Cox, Gerald; Harris, Jonathan; Altrabulsi, Basel
Abstract: Background: Serology assays have the potential to support RT-PCR in the diagnosis of SARS-CoV-2 infection. We studied three commercially available immunoassays for their diagnostic accuracy from blood specimens collected from 93 patients. Methods: Blood samples from patients with confirmed COVID-19 infection were analysed using three different Immunoassays (Roche total antibody assay, Abbott IgG assay and Euroimmun IgG assay). Sensitivity, specificity, precision and time of seroconversion were evaluated. Results: The sensitivity of Roche, Abbott and Euroimmun assays was 38.7%, 35.5% and 25.0% respectively for specimens collected <10 days and 84.4%, 84.4% and 70.0% respectively for specimens collected ≥10 days after the first positive RT-PCR. The specificity of all the three assays in this study was 100%. The timing of seroconversion occurred at day 1, 7 or 14. Conclusions: The assays evaluated in this study have different sensitivities for detecting antibodies in SARS-CoV-2 infection. Sensitivity for detecting antibodies for all three assays was higher for specimens collected ≥10 days after first positive PCR compared with specimens collected <10 days. Time of seroconversion is variable and assay-dependent.